A deadly prescription: combination of methotrexate and trimethoprim-sulfamethoxazole - Mohsin Hamid; Bilal Lashari; Irfan Ahsan; Ida Micaily; Usman Sarwar; Joseph Crocetti (Greater Baltimore Medical Center, 2018)
Methotrexate (MTX) is a chemotherapeutic synthetic(s) phase cell cycle inhibitor, and its role has evolved as an immunological agent in autoimmune diseases like rheumatoid arthritis, psoriasis, and systemic lupus erythematosus, etc. Trimethoprim-sulfamethoxazole (TS) is one of the most widely prescribed antibiotics commonly used for urinary tract infections, exacerbations of chronic bronchitis, traveler's diarrhea, and pneumocystis pneumonia. Both MTX and TS can have significantly overlapping side effects involving dermatologic, renal, and hematological systems, and the combination of these can be deadly. Our case is about the combination of MTX and TS that leads to mucocutaneous ulceration, leukopenia, and renal insufficiency. The purpose of this case is to increase awareness of potentially significant toxicity from the combination of MTX with TS. Abbreviations: MTX: methotrexate; TS: trimethoprim-sulfamethoxazole; ED: emergency department; IV: intravenous; GI: gastrointestinal; NSAIDs: nonsteroidal anti-inflammatory drugs.